MENGENAL PRIBADI MELALUI PSIKOLOGI KEPRIBADIAN - Syafrida Siregar, Lis Yulianti (IAIN Padangsidimpuan, 2013)
Personal psychology is a branch of psychology science that explains about personality. Personality is all behaviour and habitual characteristics ofÂ individual that collected within itself and it is used to react and also be able to adapt to all of stimulations, both inside or outside from behaviour and habitual are characteristics. This is a functional unity especially for someone